Social Media Activities and Consumer Purchase Regret in Delta State, Nigeria: A Serial Mediation of Brand Credibility and Brand Trust - Uzoma Ononye; Perpetual Ekpeni; Nwanne Okwechime (Binus Business Review, 2025)
Consumer purchase regret, a post-purchase evaluation outcome, is one of the challenges faced by both businesses and consumers in the social media environment. The purpose of the research was to examine how social media activities minimized consumer purchase regret by accounting for the mediation of brand credibility and brand trust. The research employed the use of cross-sectional data obtained from 278 undergraduates of Delta State University, Nigeria, who had one or more online purchase experiences. The research also utilized the Partial Least Squares (PLS) method for Structural Equation Modeling (SEM), which was used for data analysis and hypothesis testing. From the PLS results, the research finds that social media activities do not significantly reduce consumer purchase regret. However, they do when brands develop their credibility and trust levels. It also finds that the interplay between brand credibility and brand trust contextualizes the reduction effect of social media activities on consumer purchase regret in a sequential framework. The results acknowledge the significant roles of contextual factors, offering practical insights for managers and consumers seeking to reduce the likelihood of purchase regrets by leveraging credibility and trust on the social media environment. The originality of the research lies in its attempt to determine the contextual factors that amplify the negative link between social media activities and consumer purchase regret, grounded in the Stimulus-Organism-Response (SOR) framework.